Polyoxyl 60 hydrogenated castor oil free nanosomal formulation of immunosuppressant Tacrolimus: Pharmacokinetics, safety, and tolerability in rodents and humans - Ali, Shoukath M.; Ahmad, Ateeq; Sheikh, Saifuddin; Ahmad, Moghis U.; Rane, Rajendar C.; Kale, Prashant; Paithankar, Mahesh; Saptarishi, Dipak; Sehgal, Ashish; Maheshwari, Kirti; Ahmad, Imran (International immunopharmacology, 2010)
Develop Nanosomal formulation of Tacrolimus to provide safer alternative treatment for organ transplantation patients. Investigate safety, tolerability and pharmacokinetics of Nanosomal Tacrolimus formulation versus marketed Tacrolimus containing polyoxyl 60 hydrogenated castor oil (HCO-60) that causes side effects. Nanosomal Tacrolimus was prepared in an aqueous system. The particle size was measured by Particle Sizing Systems and structure morphology was determined by freeze-fracture electron microscopy. Investigational safety studies were conducted in mice and rats. Safety and pharmacokinetics of Nanosomal Tacrolimus were also evaluated in healthy human subjects. The morphology of Nanosomal Tacrolimus showed a homogeneous population of nanosized particles with mean particle size of less than 100 nm. A 14 day consecutive administration of Nanosomal Tacrolimus up to 5 and 10 mg/kg dose in rats and mice respectively, resulted in no mortality. Nanosomal Tacrolimus in human studies showed that it is safe and the pharmacokinetics profile is similar to the marketed HCO-60 based Tacrolimus. No significant change in peripheral blood lymphocyte percentage was noted in either mice or healthy human male subjects. Nanosomal Tacrolimus is well characterized product which provides a new treatment option. It contains no alcohol or surfactants like HCO-60. Thus, Nanosomal Tacrolimus presents a new and improved therapeutic approach for organ transplant patients compared to the marketed HCO-60 based Tacrolimus product.